AFM studied the effect of celastrol on β1 integrin‐mediated HUVEC adhesion and migration. Issue 5 (12th December 2012) - Ke, Changhong; Jin, Hua; Cai, Jiye
Summary Integrin‐mediated human umbilical vein endothelial cells (HUVECs) adhesion to the extracellular matrix plays a fundamental role in tumor‐induced angiogenesis. Celastrol, a traditional Chinese medicine plant, has possessed anticancer and suppressed angiogenesis activities. Here, the mechanism underling the antiangiogenesis capacity of celastrol was investigated by exploring the effect of celastrol on β1(CD29) integrin‐mediated cell adhesion and migration. Flow cytometry results showed that the HUVECs highly expressed CD29 and cell adhesion assay indicated that celastrol specifically inhibited the adhesion of HUVECs to fibronectin (FN) without affecting nonspecific adhesion to poly‐L‐lysine (PLL). After cell FN adhesion being inhibited, the cell surface nanoscale structure and adhesion force were detected by atomic force microscope (AFM). High‐resolution imaging revealed that cell morphology and ultrastructure changed a lot after being treated with celastrol. The membrane average roughness (Ra) and the major forces were decreased from 31.34 ± 4.56 nm, 519.60 ± 82.86 pN of 0 μg/ml celastrol to 18.47 ± 6.53 nm, 417.79 ± 53.35 pN of 4.0 μg/ml celastrol, 10.54 ± 2.85 nm, 258.95 ± 38.98 pN of 8.0 μg/ml celastrol, respectively. Accompanying with the decrease of adhesion force, the actin cytoskeleton in the cells was obviously disturbed by the celastrol. All of these changes influenced the migration of HUVECs from the wound‐healing migration assay. Taken together, our results suggest that celastrol can be as an inhibitor of HUVEC adhesion to FN. This work provides a novel approach to inhibition of tumor angiogenesis and tumor growth. SCANNING 35:316‐326, 2013. © 2012 Wiley Periodicals, Inc.